High Efficiency pHEMT Balanced Power Amplifier Design Using Load Pull Technique - Vijayakumaran, Lokesh Anand (2011)
A rapid increase in transmission capacity is required to meet the needs of the multimedia society. In broadband power amplifier design, a key element is maintaining flat gain across band while providing good efficiency and high output power. Commonly this is addressed using the single stage amplifier design. But in reality, to achieve high efficiency while maintaining good output power usually not practical with a single stage amplifier design. Alternatively, few stages of amplifier can achieve this and this is the point where balanced amplifier design comes into picture. Implementation of the push pull configuration using uniplanar technology is very desirable for microwave as it can create a high performance low cost compact amplifier.